2y-[3z-{4(y-2z)-5y-z)}-9y]

Question

Asked 4/27/2009 5:24:25 PM

Updated 3/29/2015 2:32:30 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

s

Expert answered|suger30ha|Points 0|

Expert answered|suger30ha|Points 0|

Expert answered|suger30ha|Points 0|

Question

Asked 4/27/2009 5:24:25 PM

Updated 3/29/2015 2:32:30 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Rating

8

2y - [3z - {4(y - 2z) - 5y - z)} - 9y]

= 2y - [3z - {4y - 8z - 5y - z)} - 9y]

= 2y - [3z + y + 9z - 9y]

= 2y - 12z + 8y

= 10y - 12z

= 2y - [3z - {4y - 8z - 5y - z)} - 9y]

= 2y - [3z + y + 9z - 9y]

= 2y - 12z + 8y

= 10y - 12z

Added 3/29/2015 2:32:28 AM

This answer has been confirmed as correct and helpful.

36,376,666

questions answered

There are no comments.